CUSTOMER RELATIONSHIP MANAGEMENT PT. SAMSUNG ELECTRONICS INDONESIA DI TENGAH PANDEMI COVID-19 DI INDONESIA - Wahdian -; Sri Dwi Setiawati (Ilmu Komunikasi, FISIP Universitas Pasundan, 2020)
ABSTRACT Samsung Indonesia as one of the big companies affected by the covid-19 phenomenon approached customer relationship management approach by making the program